Innovative determination of phytohormones in Aloe vera - Hakeem, Muhammad K.; Maraqa, Meera; Elangovan, Sampath K.; Saeed, Esam Eldin; Mishra, Ajay Kumar; Hazzouri, Khaled M.; Shah, Iltaf; Amiri, Khaled M. A. (Frontiers in Chemistry, 2025)
IntroductionAloe vera is widely known for its therapeutic properties, but concerns regarding the levels of phytohormones and their potential impact on human health highlight the need for advanced analytical techniques. This study aims to develop and validate a sensitive method for the determination of six key phytohormones in Aloe vera using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS).MethodsA validated LC-MS/MS method was optimized for the determination and quantification of six phytohormones in Aloe vera: Abscisic Acid (ABA), Salicylic Acid (SA), Indole-3-Acetic Acid (I3AA), Gibberellic Acid (GA), 6-Benzylaminopurine (6BAP), and Isopentenyladenine (ISA). The sample extraction process and mobile phase composition were optimized to enhance chromatographic separation and mass spectrometry sensitivity. A C-18 column was used for separation, and a triple quadrupole mass spectrometer was employed for quantification. The method’s performance was assessed in terms of linearity, sensitivity, and limits of detection.ResultsThe LC-MS/MS method exhibited excellent linearity (R2 > 0.99) and low limits of detection for all six phytohormones. Four of the six analytes were identified as predominant in Aloe vera. Quantitative analysis showed that ABA was the most abundant phytohormone, with a median concentration of 8.39 ng/mL, followed by I3AA (4.32 ng/mL), SA (3.16 ng/mL), and GA (1.55 ng/mL).DiscussionThis study provides a comprehensive and validated LC-MS/MS method for profiling phytohormones in Aloe vera. The results underscore the significant role of ABA, I3AA, SA, and GA in the plant's hormonal profile, offering a valuable tool for the analysis of phytohormonal content in Aloe vera and other plant species. The method is particularly beneficial for addressing health-related concerns regarding the presence and concentration of phytohormones in Aloe vera.